2005
DOI: 10.1042/bj20050375
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced laminin binding by α-dystroglycan after enzymatic deglycosylation

Abstract: Carbohydrate modifications are clearly important to the function of alpha-dystroglycan but their composition and structure remain poorly understood. In the present study, we describe experiments aimed at identifying the alpha-dystroglycan oligosaccharides important for its binding to laminin-1 and carbohydrate-dependent mAbs (monoclonal antibodies) IIH6 and VIA4(1). We digested highly purified skeletal muscle alpha-dystroglycan with an array of linkage-specific endo- and exoglycosidases, which were verified fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 38 publications
2
67
0
Order By: Relevance
“…S8). Although the enzymatic activities of LARGE remain to be characterized, one report suggests that an unidentified anionic modification on α-dystroglycan may supply the functional groups needed for ligand-binding activity (25). Interestingly, the binding of laminin α1 to α-dystroglycan depends on clusters of basic amino acid residues located on the surfaces of its LG domains (26).…”
Section: Discussionmentioning
confidence: 99%
“…S8). Although the enzymatic activities of LARGE remain to be characterized, one report suggests that an unidentified anionic modification on α-dystroglycan may supply the functional groups needed for ligand-binding activity (25). Interestingly, the binding of laminin α1 to α-dystroglycan depends on clusters of basic amino acid residues located on the surfaces of its LG domains (26).…”
Section: Discussionmentioning
confidence: 99%
“…Using CHO CELL mutants, Patnaik and Stanley have shown that LARGE does not require sialic acid, galactose or fucose to glycosylate α-dystroglycan. 59 Similarly, Combs and Ervasti have shown that enzymatic removal of sialic acid, galactose and N-acetylglucosamine from α-dystroglycan actually stimulates its binding to laminin, 60 much as LARGE overexpression does. 57 Again, this evidence indicates that these carbohydrates are not synthesized by LARGE.…”
Section: Dystroglycanopathy-gene Function: Some Mysteries Remainmentioning
confidence: 97%
“…In these disorders, ␣-DG lacks laminin-binding activity (17); therefore, the tetrasaccharide plays an important role in the post-translational maturation of ␣-DG as a laminin receptor. On the other hand, recent studies have suggested that the Neu5Ac-␣2,3-Gal-␤1,4-GlcNAc branch on O-mannose per se is not likely the lamininbinding glycan of ␣-DG (12,18).…”
Section: Dystroglycan (Dg)mentioning
confidence: 99%